Correlation between Fusarium graminearum and Deoxynivalenol during the 2012/13 wheat fusarium head blight outbreak in Argentina - Palazzini, Juan Manuel; Fumero, María Verónica; Barros, Germán Gustavo; Yerkovich, Nadia; Cuniberti, Martha Beatriz; Chulze, Sofia Noemí (2018)
Fusarium graminearum (Schwabe) is reported as the main causal agent of Fusarium head blight in Argentina. The disease causes great losses in humid and semi-humid regions of the world, reducing grain yield and quality. During 2012/13 harvest season, a severe epidemic occurred in Argentina. The aims of this work were to determine the F. graminearum incidence and deoxynivalenol accumulation in wheat grain and flour samples obtained from two of the main wheat growing regions from Argentina. Levels of the pathogen and deoxynivalenol content were correlated in heads, grains and flour. Out of 69 wheat grain samples, 55 (79.7%) showed deoxynivalenol levels between 0.4 and 8.5 μg/kg. Fusarium graminearum was the main species isolated, the isolation frequency ranged from 30 to 52% of the total grains analyzed. Correlations were observed between deoxynivalenol content, % of F. graminearum infection, presence of the pathogen in heads, grain and flour.